High-acclimation capacity for growth and role of soil fertility after long-range transfer of Betula pendula and B. pubescens between Finland and Italy - Oksanen, Elina; Silfver, Tarja; Ghelardini, Luisa; Pecori, Francesco; Nieminen, Kaisa; Ruhanen, Helena; Rousi, Matti; Santini, Alberto; Mikola, Juha (Springer Nature, 2025)
The acclimation capacity of Betula pendula and Betula pubescens was studied over 4 years in common gardens in central Italy (43° N) and southern (61° N) and northern Finland (67° N), representing drastically different photoperiod and climate in temperate, boreal and subarctic vegetation zones. Two study sites that differed in soil fertility were established at each location, giving a total of six common gardens. The birch material was micropropagated from naturally regenerated stands of B. pendula and B. pubescens from Susa Valley and Rochemolle Valley in northern Italy, Punkaharju in southern Finland and Kittilä in northern Finland. The plants were measured for height growth, stem diameter, leaf chlorophyll content, leaf herbivory and pathogen damage. The effects of soil fertility on the common garden results were also analyzed. The results showed high acclimation capacity of B. pendula and B. pubescens after a long-range transfer from southern to northern Europe, despite the major shift in climate and photoperiod. First-year growth on average was best in boreal southern Finland for all origins. Betula pendula grew more than B. pubescens in Italy and southern Finland, while B. pubescens grew more in northern Finland and better tolerated the northward transfer. The height growth of origins showed a clear latitude gradient from slowly growing northern to fast growing southern origins in the nursery and laboratory, but not in the field. Soil fertility explained a significant part of variation among locations not only for growth variables, but also for leaf chlorophyll content and leaf herbivory and pathogen damage. Leaf herbivore and pathogen damage was greatest in southern Finland. Our results demonstrate good survival of birch from northern Italy in Finnish conditions and support the possibility of long-range south-to-north transfer of Betula species to provide resistant planting material in boreal forests for the rapidly changing climate.
Keywords: birch; Betula sp.; common garden; climate warming; herbivory